(untitled) (International Journal of Physiotherapy, 2020)
Background: Adhesive Capsulitis (AC) of the shoulder joint is a chronic disabling musculoskeletal condition affecting 2% to 5.3% of the world’s general population. It results in pain, restricted ROM, impaired myofascial kinetics due to fibrosis of capsules and ligaments. Myofascial trigger points (MTrPs) that could further restrict shoulder movements by inducing girdle muscle tightness. MTrP dry needling (MDN) intervention and other conservative therapies in subjects with AC of the shoulder would enhance the clinical outcome. However, insufficient evidence available to support the local MDN with paraspinal dry needling (PSDN) for the AC management. The study’s objective is to evaluate the efficacy of local MDN with and without PSDN in AC patients. Methods: A total of 210 (98 male, 112 female) clinically diagnosed subjects with AC were recruited from a multi-specialty hospital and then randomly assigned to one of three groups. G1: Local MDN group (n=70) G2: Local MDN with PSDN group (n=70) G3: Conventional physiotherapy group (n=70). The outcome measures included pain intensity (VAS), shoulder ROMs (Goniometer), disability (SPADI), and pressure pain threshold (pressure algometer) were assessed at baseline and 12th day of the intervention. Results: The statistically significant (p < 0.05) improvement in all shoulder ROMs (except lateral rotation), pain intensity, SPADI, and PPT in “G1” and “G2” compared to “G3” but no significant difference in between “G1” and “G2”. Conclusion: Local MDN is an effective treatment technique and conventional physiotherapy intervention, but PSDN does not have an additive effect on outcome measures in AC subjects.